Pattern of opioid prescriptions among patients with breast, lung, and colorectal cancer diagnosed with pre-existing chronic non-cancer pain - Safalta Khadka; J Douglas Thornton; Khalid M Kamal; Gerald Higa; Kimberly M. Kelly; Sabina O. Nduaguba (PLoS ONE, 2026)
Background Chronic non-cancer pain (CNCP) due to comorbid conditions presents a barrier to optimal pain management in patients with cancer. While opioid is widely used for the treatment and management of CNCP, it is also associated with misuse and addictions. Therefore, we determined the impact of CNCP on opioid prescribing patterns in patients with the three most common cancer types- breast, lung, and colorectal cancers. Methods A retrospective cohort study was conducted utilizing Surveillance Epidemiology and End Results (SEER)-Medicare (2006–2019) linked database. Patients, at least 66 years old with histologically confirmed incidental diagnoses of breast, lung, or colorectal cancer from 2007 to 2017, were included in the study. Patients with cancer in baseline period, in palliative care, or those who died in the follow-up period were excluded from the study. Patients with CNCP were identified in the baseline period. Patients without CNCP during the study period were included in the no-CNCP group. The follow-up period was one year after cancer diagnosis (index date) and the primary outcome was opioid prescribing patterns defined as: any opioid use, high-dose opioid use, total count of opioid prescriptions filled, and chronic opioid use. Inverse probability weighting (IPTW) method was used to balance the covariates (age at the cancer diagnosis time, sex, race, ethnicity, marital status, cancer type, cancer stage, metropolitan status, year of cancer diagnosis, chronic cancer-treatment-related pain, neoplasm pain, and cancer treatment modalities) between the CNCP and no-CNCP group. Logistic and Poisson regressions were used to compare opioid use and opioid prescription patterns among the two groups. Results A majority of patients included in the study were breast cancer (CNCP = 38230, no-CNCP = 56157), lung cancer (CNCP = 17255, no-CNCP = 24602), colorectal cancer (CNCP = 16660, no-CNCP = 29037). Among cancer patients, the prevalence of CNCP was highest in those with lung cancer (41.2%) followed by breast cancer (40.1%) and colorectal cancer (36.4%). Descriptive analysis demonstrated patients with lung cancer had consistently higher rates across opioid prescribing patterns, followed by patients with colorectal and breast cancer. The result of logistic regression after weighting showed that the odds of any opioid use were higher among lung cancer patients with CNCP (OR 1.5; 95% CI 1.5–1.6; p < 0.01) compared to the no-CNCP group with lung cancer. Patients with breast cancer and CNCP had higher odds of chronic opioid use followed by lung cancer and colorectal cancer (OR 2.7; 95% CI 2.6–2.8; p < 0.01, OR 2.4, 95% CI 2.3–2.5; p < 0.01, and OR 2.4; 95% CI 2.3–2.5; p < 0.01) respectively compared to patients without CNCP but respective cancer. Conclusion CNCP adds an additional burden in opioid prescription in active cancer patients which necessitates a meticulous approach to opioids prescribing.